Low-power inductorless current-reuse LNAs with active and passive Gm-enhancement. (March 2020) - Chaghaei, Javad; Jalali, Ali; Meghdadi, Masoud
Abstract: In this paper, two low-power inductorless low-noise amplifiers (LNAs) for multi-standard wireless applications are presented. In the first proposed design, the outputs of two complementary NMOS and PMOS common-gate stages are combined to reduce the power consumption and to facilitate the dc biasing. Also, passive G m -boosting is applied to the core transistors to improve the noise performance. As a result of these techniques, a minimum NF of 2.6 dB is achieved, while consuming only 1 mA from the 1.8 V supply. In the second proposed design, both active and passive G m -boosting techniques are applied to the input complementary CG stages to enhance the voltage gain. As a result and by consuming only 1.2 mA, the second LNA achieves a higher voltage gain of 27.9 dB, with the same 3-dB bandwidth.